Introduction to the Climate Data Tool (CDT): Remote Training with Ethiopian Universities - Grossi, Amanda; Faniriantsoa, Rija; Belay, Berhanu; Dinku, Tufa; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A remote six-day training on the Climate Data Tool (CDT) was convened from January 23 to January 30, 2023, with universities across Ethiopia by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School, in close collaboration with the International Livestock Research Institute (ILRI). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 27 participants from 9 universities across Ethiopia (and 1 outside of Ethiopia) to install CDT on their operating systems and practice navigating its interface to perform a number of basic analyses and visualizations of climate data at given locations. CDT is a free, open-source, R-based software with an easy-to use graphical user interface used in Ethiopia and 23 other primarily African countries. This software ensures quality-control of rainfall and temperature observations, alongside the performance of an array of analyses and visualization capabilities that are important for tailoring and communicating climate information.